Optimization and scale up of the enzymatic hydrolysis of Californian red worm protein (Eisenia foetida) (2023)
ABSTRACT: Although the best-known use of the different species of earthworm is the production of organic fertilizer, they can also be considered a rich source of biologically and pharmacologically-active compounds, for use in the treatment of various diseases. In recent decades, with the development of biochemical technologies, research on the pharmaceutical effects of compounds extracted from different species of earthworms has begun. Enzymatic hydrolysis is the most common and widely used technique for producing bioactive hydrolysates, because it uses moderate operating conditions, with a certain specificity for the substrate. In the present study, the objective was to optimize and scale up the enzymatic hydrolysis of Eisenia foetida protein to obtain peptides with biological activity. The substrate characterization was carried out according to AOAC, a response surface design was performed for the optimization of the enzymatic hydrolysis and then the scaling was performed by means of dimensional analysis. The results show that the major component of the paste is protein, 65% of which is albumin, and the absence of pathogenic microorganisms was also found. Regarding optimization, it was found that the optimal hydrolysis conditions are achieved with pH = 8.5; temperature = 45 ◦C; amount of substrate = 125 g and volume of enzyme = 1245μL. For the scaling, 4 dimensionless pi-numbers were calculated which describe the process with no statistically significant differences between the model and the prototype; it can be concluded that the enzymatic hydrolysate of Eisenia foetida presents high values of antioxidant activity evaluated by different methodologies.